2003
DOI: 10.2307/3090274
|View full text |Cite
|
Sign up to set email alerts
|

Who Goes to Graduate School? Social and Academic Correlates of Educational Continuation after College

Abstract: Although sociologists have found direct links between parents' education and the high school and college educational attainments of their offspring, researchers have been surprised to find no parental effects on educational enrollments beyond college. Postgraduate matriculation appears to result from academic success in college, divorced from parents' educational capital. Using new data from the Baccalaureate and Beyond Longitudinal Study, the authors reexamine this issue and extend the literature by disaggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
238
4
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(272 citation statements)
references
References 35 publications
(18 reference statements)
14
238
4
10
Order By: Relevance
“…Specifically, the more formally educated a student's parents are, the more likely the student applies to and enrolls in graduate school. For example, Mullen, Goyette, and Soares (2003) found that parental education is important for enrollment. In particular, the researchers found significant differences between parental education and students' enrollment into graduate school.…”
Section: Family Statusmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, the more formally educated a student's parents are, the more likely the student applies to and enrolls in graduate school. For example, Mullen, Goyette, and Soares (2003) found that parental education is important for enrollment. In particular, the researchers found significant differences between parental education and students' enrollment into graduate school.…”
Section: Family Statusmentioning
confidence: 99%
“…Several researchers have evaluated the influence of undergraduate academic achievement on post-baccalaureate enrollment (Baird, 1976;Ethington & Smart, 1986;Mullen, Goyette, & Soares, 2003;Zhang, 2005). In general, students who are successful academically during undergraduate education are more likely to continue their education in graduate school.…”
Section: Academic Abilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Studien aus den USA, die den Zugang zu verschiedenen Formen postgradualer Bildung in Abhängig-keit von der sozialen Herkunft untersuchen, kommen teilweise zu widersprüchlichen Ergebnissen (Ethington & Smart 1986;Mare 1980;Mullen et al 2003;Stolzenberg 1994). In einer älteren Untersuchung fand Mare (1980), dass der Effekt der sozialen Herkunft von der Highschool bis zum postgradualen Studium mit dem Erreichen jeder nächst hçheren Bildungsstufe immer weiter abnimmt.…”
Section: Bisherige Forschungsergebnisseunclassified